Drivers of Change in National Disaster Governance under the Hyogo Framework for Action - Wanner, Maximilian S. T. (2020)
Many suggestions have been made on what motivates countries to expand their measures for disaster risk reduction (DRR), including the frequency and severity of natural hazards, accountability mechanisms, and governance capacity. Despite the fact that theoretical arguments have been developed and evidence collected from small-scale case studies, few studies have attempted to explain the substantial variation in the adoption of DRR measures across countries. This study combines available data on DRR measures, natural hazard events, governance, and socioeconomic characteristics to provide a systematic assessment of the changes that have occurred in the state of DRR at the national level. In line with theoretical explanations, there are indeed associations between several measures of frequency and severity and the development of DRR status. Additionally, voice and accountability mechanisms, as well as development aid, might facilitate positive change. Although these first results of a global comparative study on change in DRR have to be taken cautiously, it is a step forward to understanding the drivers of change at the national level.